TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN ZAKAT DALAM MENINGKATKAN KEPERCAYAAN MUZAKKI DI DESA SEKUMBUNG KECAMATAN TAMAN RAJO KABUPATEN MUARO JAMBI - M Wildan; Hansen Rusliani; Nurlia Fusfita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study aims to determine how the transparency and accountability of zakat management in increasing the trust of muzakki in Sekumbung Village, Taman Rajo District, Muaro Jambi Regency. The theory used in this study is the theory put forward by Djarwanto that Accountability provides, conveys information by being responsible for performance in the form of success or failure to achieve the goals set. Meanwhile, transparency was stated by Farid Hamid, namely seeking, receiving, possessing, storing, managing, and sending information through all available channels. The type of this research is descriptive qualitative with primary and secondary data types. Data collection techniques in this study are using questionnaires, observation, interviews and documentation, while for data analysis, researchers use domain, textonomy and componential analysis. The results of the study explain that the transparency of zakat management in increasing the trust of muzakki in Sekumbung Village, Taman Rajo District, Muaro Jambi Regency can be seen from several aspects, namely the role of Amil Zakat in coordinating zakat funds to the community directly and maximizing the disclosure of zakat management information by making periodic reports on performance and activities. zakat management. Accountability of Zakat Management to Increase Muzakki Trust in Sekumbung Village, Taman Rajo District, Muaro Jambi Regency can be seen from several aspects including the existence of amil zakat activities in making financial reports in writing. The existence of activities to prepare financial reports with a simple accounting system as a form of accountability for the performance carried out. The existence of amil zakat efforts in improving the ability and moral quality in managing zakat.